ANALISA PENDAPATAN MASYARAKAT YANG MEMANFAATKAN HUTAN MANGROVE DI DESA OLAK-OLAK KECAMATAN KUBU KABUPATEN KUBU RAYA - liyasari, April; Lumangkun, Augustine; Natalina, Uke (Universitas Tanjungpura, 2016)
In the tropics, mangroves are rich in flora and fauna. This rich forest ecosystems provide a wide range of products and services both economically and environmentally. The research was conducted in the village of Olak-olak Kubu Sub District, Kubu Raya District, from February to May 2014. The aims of this research are to determine: the income level of community who uses forest products from mangrove forests, the contribution of mangrove forest products to household income, and the factors that affect income of household who use mangrove forests. The study used survey methods to the local people as respondents who use mangrove forests as income. The number of respondents are 40 families or households.The research showed that the average income of respondents are Rp. 12,841,601.00 per family per year. The results are from timber for building, fish, shrimp, crabs and clams. While revenues from outside mangrove forests that are obtained from farming, gardening, livestocking and others are Rp. 3,264,125.00 per families per year. The contribution of mangrove forests is 81% of the total revenue. Factors age level (X1), working hours (X2), the kinds of result (X3) and experience (X4) were not give significantly on revenue ie with Fcount = 0868